Severe ectrodactyly in dog – Case report - Martinelli, Emaira Caroline Castelo; Vasques, Gabriela Maria Benedetti; Leal, Leonardo Martins; Garcia Filho, Sérgio Pinter; Romani, Isaac (Research, Society and Development, 2020)
Ectrodactyly is a malformation that consists of a separation between the soft tissues and distal bone portions of the limbs, which may occur either unilateral or bilateral, with the former being more frequent. The origin of this malformation is still unknown. Reports describe that ectrodactyly may be hereditary, but information is sparse in the literature. It is diagnosed through anamnesis, physical examination and, mainly, radiography. The therapeutic approach to be adopted depends on the extent of the lesion in the affected limb, and it is possible to choose between orthopedic correction or the amputation of said limb. This study reports the case of a mongrel male puppy – the result of an inbreeding between “mother and son” – with a malformation in its right thoracic limb. The animal showed pain from having the limb palpated, claudication without the support of the limb, and muscle atrophy. After follow-up and radiographic evaluation, severe malformation was detected, requiring the amputation of the limb. Through a karyotype test, a normal set for the species was found, 2n = 78, XY, with the occurrence of chromosomal mutation associated with the malformation being excluded. After the surgical procedure, the limb was dissected, which allowed confirming, by means of radiography, the separation of the soft and bone tissues of the radius and the ulna extending through the carpal and metacarpal bones, then reaching their respective phalanges, characterizing ectrodactyly in the right thoracic limb and aplasia of two metacarpal bones. La ectrodactilia es una malformación que consiste en la separación de tejidos blandos y de porciones óseas distales de los miembros, pudiendo ocurrir de forma unilateral o bilateral, siendo la unilateralmente con mayor frecuencia. El origen de esa malformación es aún desconocido. Relatos describen que la ectrodactilia pueda ser de origen hereditario, pero las informaciones son pocas en la literatura. El diagnóstico se da a través de la anamnesis, examen físico y principalmente examen ...